KAJIAN WILAYAH PENGENDALIAN RUANG KAWASAN DANAU TEMPE, PROVINSI SULAWESI SELATAN - Ari Djatmiko; Deden Syarifudin; Meyliana Lisanti (Moderat : Jurnal Ilmiah Ilmu Pemerintahan, 2023)
Problem utilization room often occurred in the area around Situ, Lake , Embung And Reservoir (SDEW) in the form of happen occupation body of water, decline water quality , and nonconformity utilization space in the area SDEW boundaries as well around SDEW area . By Because that is necessary study supporter form identification region surrounding control _ lake as part from load device control utilization room in accordance with Candy Agrarian and Spatial Planning / Head Body Land National Number 21 of 2021 concerning Implementation Control Utilization Room And Supervision Structuring Room . In accordance Candy considerations are also included _ formulation identification region control based on on 5 ( five ) aspects study form concentration utilization space , level embodiment space , power support land , domination utilization room And impact negative that arises . Although Thus , the analysis process fifth aspect study the Not yet explained in a way detailed with rule or instruction control utilization more space _ technical . More far away , identify region control utilization room with consider fifth aspect study Still limited studied on a number of studies previous . Based on problem above , goal study This is For find out region control utilization space around _ Tempe Lake in South Sulawesi Province will done with determine zone control And zone pushed through identification concentration utilization space , level embodiment space , power support land , domination utilization space , and impact negative . As for method approach through formulation background behind And problem , formulation objectives , survey , compilation And data analysis as well embodiment product study . As for results analysis region control Lake Tempe shows part big dominated Zone Full /ZK ( as much as 10ZK) and only 1 Zone Driven (ZD).